Tourism and Indigenous Peoples : Lessons from Recent Experiences in Eco and Ethno Tourism in Latin America and the Caribbean - Verner, Dorte; Maria Solo, Tova (World Bank, Washington, DC, 2012)
The trend toward new tourism niches in Latin America and the Caribbean (hereafter, LAC) has brought benefits, but also costs to the region's indigenous peoples. As the World Bank social and environmental portfolios in LAC reveal, work with indigenous groups has frequently favored tourism as a strategy for empowerment. At the same time, urban, rural development and infrastructure projects have also increased tourism opportunities, including visits to indigenous communities. Bank experience indicates the increasing need for dialogue and greater understanding of the issues involved in these cases. This en breve offers an overview of the concerns generated by 'ethno-tourism' and, through consultation with three experts who have worked with indigenous groups in Argentina, Brazil and Colombia, proposes approaches recommended to reduce negative impacts.